From Mattering to Mattering More: ‘Goods’ and ‘Bads’ in Ageing and Innovation Policy Discourses - Greubel, Carla (Int J Environ Res Public Health, 2021)
This paper provides an empirical ethics analysis of the goods and bads enacted in EU ageing and innovation policy discourses. It revolves around a case study of the persona Maria, developed as part of the EU’s Active and Healthy Ageing Policies. Drawing on Pols’ empirical ethics as a theoretical and methodological approach, we describe the variety of goods (practices/situations to be strived for) and bads (practices/situations to be avoided) that are articulated in Maria’s persona. We analyse how certain ideas about good and bad ageing—those associated with the use of sophisticated technologies—come to matter more in the solutions proposed for Maria and the framing of her unmet needs, while others which were initially seen as relevant and that describe her dreams, fears and interactions, are marginalised. The paper adds to existing studies of ageing and technology by analysing specific practices that render visible how the idea of technology and data sharing as evidently the right path towards futures of (good) ageing, comes to prevail.